Gendered wealth losses after dissolution of cohabitation but not marriage in Germany - Diederik Boertien; Philipp M. Lersch (Deutsches Institut für Wirtschaftsforschung (DIW), 2019)
Objective: To document gender differences in how economic wealth changes following the dissolution of marriage and cohabitation in Germany. Background: Wealth can be an important resource to deal with the adverse economic consequences of union dissolution. Marital property regimes usually ensure that both partners receive a share of the couples' wealth following a divorce. The dissolution of cohabiting unions is not governed by such rules in most countries, including Germany, which may lead to a more unequal division of wealth following the dissolution of cohabitation as compared to marriage. Method: The analysis consists of multivariable fixed-effects regression models based on longitudinal data from the German Socio-Economic Panel (N = 6,388 individuals) for the years 2002 to 2017. Results: Changes in wealth are relatively similar for men and women after the dissolution of marriage. The dissolution of cohabiting unions is related to losses in wealth for women, but not for men. Controlling for post-dissolution processes, gender inequality increases after the dissolution of cohabitations. Conclusion: Union dissolution is associated with wealth losses. The legal protection of the economically weaker spouse in marriage prevents gender inequality in these wealth losses. Lacking such legal protection, cohabitation is associated with gender inequality in the consequences of dissolution.
Keywords: 330